Efficacy of Psycho-Cardiology therapy in patients with acute myocardial infarction complicated with mild anxiety and depression - Chen, Xiaoliang; Zeng, Mengya; Chen, Chen; Zhu, Dan; Chen, Li; Jiang, Zuying (Frontiers in Cardiovascular Medicine, 2023)
Objective: To evaluate the efficacy of Psycho-Cardiology therapy among patients with acute myocardial infarction (AMI) complicated with mild-to-moderate anxiety and depression. Methods: Two hundred and fifty-six patients with AMI who were admitted to the Cardiovascular Department of Chenzhou First People's Hospital from January 2018 to January 2020 were selected as subjects, and randomly divided into the control group (n= 128) and the Psycho-Cardiology treatment group (n= 128). Prior to the intervention, the general clinical data of the enrolled patients, such as gender, age, comorbidities (hypertension, diabetes) and smoking history, were compared, which revealed no statistical differences between the two groups (P> 0.05). The control group was given routine treatments such as reperfusion and secondary prevention of coronary heart disease, while the treatment group was given Psycho-Cardiology intervention in addition to the aforementioned treatments and if necessary, anxiolytics and antidepressants. Results: No significant differences in PHQ-9 and GAD-7 scores were observed between the control and treatment groups at admission (P> 0.05). After the Psycho-Cardiology treatment, the PHQ-9 and GAD-7 scores of the treatment group decreased significantly. Based on the 1-year post-treatment comparison, the left ventricular ejection fraction was improved more significantly in the Psycho-Cardiology treatment group, showing statistical significance (P< 0.05). The treatment group exhibited statistically significantly low incidences of adverse cardiovascular events, such as recurrent angina pectoris, heart failure, malignant arrhythmia, recurrent myocardial infarction and death (P< 0.05). Conclusions: Psycho-Cardiology therapy is remarkably efficacious in improving the anxiety, depression, cardiac function and reducing the occurrence of adverse cardiovascular events, which can better improve the long-term prognosis of patients with AMI compared to the traditional treatments.